Important factors in protecting young generation from spiritual threats in a remoderated Uzbekistan - Eshov Khurshid Khurramovich; Eshova Khurriyat Khurramovna (International Journal on Orange Technologies, 2021)
After the independence of the Republic of Uzbekistan, the values of national statehood, spirituality and national traditions have been restored, and democratic values have been developed in the life of society. Huge political and social work is being carried out in our country aimed at building a democratic society and civil society. As a result of globalization inherent in the XXI century, the processes of international integration are developing rapidly